Species diversity of mosquitoes of the Genus Culex (Diptera, Culicidae) in the coastal areas of the Persian Gulf - Mehdi Khoobdel; Davoud Keshavarzi; Seyed Hassan Mossa-Kazemi; Hossein Sobati (AIMS Press, 2019)
Background: Lack of information about the dispersal of vector species barricade surveillance and control. Aims: Therefore, the aim of the present study was to determine the species diversity of Culex mosquito's larvae in the coastal areas of the Persian Gulf. Methods: Mosquito larvae were collected from six places in three main environmental categories: urban (UA), rural (RA) and uninhabited areas (UNA), using dipping technique. Four dips were taken from each breeding site (350 ml each). Larval investigation was conducted two times a month during the study period. Diversity studies were conducted separately for each category by calculating classic diversity indices. Results: In total, 1369 specimens belonging to 10 different species were collected and identified, as follows: Culex hortensis, Cx. laticinctus, Cx. mimeticus, Cx. perexiguus, Cx. pipiens, Cx. modestus, Cx. sinaiticus, Cx. theileri, Cx. torrentium and Cx. tritaeniorhynchus. None of these mosquito species have been recorded previously in this region. Diversity analysis indicated higher species richness for RA (Margalef 1/26). The average diversity indices for the three environment types ranged from 1.50 to 1.64 for Shannon index and from 0.730 to 0.738 for Simpson index. Conclusions: Biodiversity analysis indicated that species diversity in rural, urban and uninhabited areas is somewhat similar. Therefore, attention to all areas in vector control programs is essential.